Legal Responsibility of Nurses for Alleged Nursing Malpractice in Hospitals - Kristanto Setyo Nugroho; Aris Prio Agus Santoso; Heri Dwi Utomo (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Nursing services are an essential component of the healthcare system in hospitals, aimed at providing professional, safe, and standardized nursing care. In practice, nurses are obligated to perform their duties in accordance with professional standards, service standards, standard operating procedures (SOPs), and the nursing code of ethics. However, there is a possibility of errors or negligence that may give rise to allegations of nursing malpractice and potentially cause harm to patients.This study aims to analyze the legal liability of nurses in relation to alleged nursing malpractice in hospitals and to examine the forms of legal responsibility that may be imposed under applicable laws and regulations. The research employs a normative legal method using both statutory and conceptual approaches through the analysis of relevant legislation, legal literature, and scientific journals.The findings indicate that nurses may be held legally accountable if they are proven to have committed acts or omissions that deviate from professional standards and result in harm to patients. Such legal liability may take the form of civil, criminal, administrative, as well as ethical and professional disciplinary responsibility. Furthermore, hospitals as healthcare institutions may also be held liable for the actions of healthcare professionals acting within the scope of their authority.Therefore, it is necessary to enhance nurses’ competencies, ensure compliance with service standards, and implement effective supervision mechanisms in order to prevent alleged nursing malpractice and to guarantee legal protection for both patients and healthcare professionals.